Analisis Pengaruh Kompetensi Pedagogik, Kepribadian dan Profesional Guru terhadap Kemampuan Akademik Siswa: Studi Kasus di Kabupaten Garut - Septiana, Vena; Rozikin , Mochamad; Sujarwoto, Sujarwoto (Jurnal Ilmiah Administrasi Publik, 2024)
The objective of this study is to identify the influence of pedagogical competence, personality competence and professional competence of a teacher on students' academic ability. Thus, teachers can design learning in accordance with the level of student development. The research methodology employed in this study is a quantitative approach utilizing a survey design. The target population for this research is class XII students at SMK Negeri 2 Garut, the sample amounted to 197 respondents, consisting of 151 men and 46 women. The findings indicated that the pedagogical and professional competencies of teachers positively and significantly impact the academic capabilities of students. However, teacher’s personality competence has no influence on student academic ability. There are several possible reasons for the absence of influence between these variables, including the different characteristics of students and teachers, where each student has a unique personality, background and learning preferences. While most students may benefit from teachers' personality competence, it is possible that some students do not respond in the same way or need different types of support.